Epidemiological study of risk factors related to childhood visceral leishmaniasis - Rukunuzzaman, M; Rahman, ME (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jan;17(1):46-50. The abstract of this article is available on the PubMed website